Interpretiranje literature v zmanjšanem merilu: »Oddaljeno branje« korpusa »dolgega leta 1968« - Juvan, Marko (Jezik in slovstvo, 2021)
This article discusses the role of interpretation in the digital humanist approach to literature, focusing on corpus analysis. It illustrates the interpretive significance of computer-based quantitative statistical analyses of tokens, tags and metadata in a small corpus of literary texts produced in a given period. Using the example of a corpus of original literary texts printed in the journals of the predominantly student generation (Tribuna and Problemi) during the international student movement of “The Long 1968”, a quantitative analysis or “distant reading” examines the assertion of modernism, the change in genre repertoire and literary language, the textual traces of the revolutionary atmosphere, and the role of women in the literary system.
Keywords: 1960–1975; corpus analysis; digital humanities; digitalna humanistika; distant reading; korpusna analiza; literarni korpus; literary corpus; oddaljeno branje; Slovenian literature; Slovenska književnost; student movement; študentsko gibanje